Potencial fitorremediador da algaroba (Prosopis juliflora (Sw.) DC) e percepção quanto aos riscos toxicológicos associados a rejeitos de mineração no semiárido brasileiro - Dutra, Albany Salustino Fernandes (2019)
Due to the serious impact caused by anthropic action through worldwide mineral extractive activity and its effects on ecosystems and human health, studies and scientific research have been carried out in order to seek solutions or ways to mitigate these impacts. The present study aimed at represent the perception of a population located in the Brazilian Semi - arid of the State of Rio Grande do Norte (RN), potentially impacted by extractive mineral activity as a factor of social and sanitary vulnerability. Then, as a way of minimizing these impacts, the phytoremediation of heavy metals from the mining using algaroba (Prosopis juliflora (SW.) DC) was tested as a plant able to remediate these elements present in the Brejuí / RN mine. The study was consolidated in two chapters, the first one, Perception of the environmental risk by population exposed to the mining activity in the Northeastern semi-arid region, in the mine community area, and the second, Phytoremediation: Prosopis juliflora (SW.). DC) as a potential phytoremediation agent for mining residues in the Brazilian Northeast semi-arid region, performed in situ in two distinct areas, mine (area 1) and farm (area 2). The methodology used was the application of semistructured forms and descriptive analysis of the observed results (chapter 1), and the use of sample collection and analysis of heavy metal contents in the environmental matrices (soil, water and plant) in the mine and on the farm, with application of descriptive analysis of the results and the correlation coefficient of Spearmam, thus verifying the association of the degree of contamination of the metals in soil, water and roots of the algaroba. After that, the phytoremediation factor was applied on each metal to confirm the phytoremediation potential of the algaroba (chapter 2). As results, it was evidenced that intellectual development is a decisive factor in the behavior and understanding of the environmental issues and the risks attributable to the polluting potential generated by the local anthropic activity, with influence on the quality of life of individuals and the environment. There were high concentrations of certain metals (Al, Cd, Ni, Co, Cr, Fe, Mn, Zn and Cu) in the different environmental compartments, so, according to the phytoremediation factor applied for each element, the algaroba phytoremediated Co > Ni > Cu > Zn >Al > Cr > Mn > Fe. The algaroba remedied metals in its roots, confirming that it is a phytoremediating plant, suggesting, by the parameter analyzed (plant root), phytostabilization as the most appropriate approach for the Brejuí mine area. The observations achieved here serve as a subsidy for future work to be aimed at ratifying or rectifying this study, which is so important in social and economic terms for the mining activities of the studied region, as well as for the better sustainability of the semi-arid region of the Brazilian Northeast.